PROFIL KECERDASAN EMOSI PESERTA DIDIK DI SMA PGRI 4 PADANG - Putri, Fitriyana (Bimbingan dan Konseling, 2014)
Emotion has a big roleÂ in action to take a rational measure. A high emotional brighthess would helping a teenager to conted with the right. Ways and make a comfortable environment. Frequent fights student indicates that the student has not been able to knowing their emotions well and others, inability to manage emotions well and has a bad communication with friends. The purpose of this research to describe: 1) intrapersonal students intelligence of Senior High School PGRI 4 Padang. 2) interpersonal students intelligence of Senior High School PGRI 4 Padang. This research uses descriptive quantitative approach. The population in this research is all of students at Senior High School PGRI 4 Padang that have 139Â person. Taking the sample uses stratified random sampling technical. The number of samples obtained by 58 person. Further that the proportional of respondents in each stratum is done by using sampling fraction (fi). Tools used for collected data in the form of a questionnaire. Techniques used To analyze the data is used a percentage. To determine score category in form interval score using the formula mean hipotetic. The results of this research found that emotional intelligence profiles of students High School PGRI 4 Padang are in good categories with apercentage of 50%. Further that intrapersonal intelligence profiles are pretty good with a percentage of 51,72%, where as the interpersonal intelligence profiles are good categories with a percentage of 65,52%. According to the interapersonal intelligence profiles of student High School PGRI 4 Padang are good better than the intrapersonal intelligence.Â